Sustained Virologic Response for Chronic Hepatitis C Infection After 27 Days of Treatment with Sofosbuvir and Ribavirin. (2nd May 2014) - Meissner, Eric G.; Nelson, Amy; Marti, Miriam; Masur, Henry; Osinusi, Anu; Kottilil, Shyam
Abstract: Successful treatment of chronic hepatitis C virus infection can now be achieved using direct-acting antiviral agents without interferon. In this report, we present a patient who achieved a sustained virologic response after 27 days of treatment with sofosbuvir and ribavirin. It is imperative to identify factors that allow for shorter treatment times in some individuals.